Penerapan Metode Job Safety Analysis and Risk Score untuk Meningkatkan Keselamatan dan Kesehatan Kerja pada Departemen Printing, Sewing dan Assembly PT. PAI, Bandung (Suatu Pendekatan Participatory Ergonomic) - Paulus Sukapto; Harjoto Djojosubroto; Handy Permana (Politeknik Kesehatan Tanjung Karang, 2018)
The footwear industry problem lies in the working environment and facilities that do not meet the standards for the health and safety of workers, necessary improvements must be made. This research was used the questionnaire and observation to evaluate the activities of the work process. The EPPEQ questionnaire was used to evaluate the level of ergonomic participation in the activities examined. In addition the questionnaire, this research was also conducted observation in order to measure the risk level of the workplace and for improving the work system using PE (participatory ergonomics). The results showed that 3 workstations have high-risk levels, 4 stations have medium risk levels and 2 workstations have a low level of risk. The results of workers participation level using the EPPEQ ergonomics questionnaire showed that the level of ergonomic activity was fairly high, but based on the linear regression, the level of ergonomic activity does not differ in terms of the footwear workshop facilities, the work environment or the safety climate. Conclusion, there were 3 workstations with a high-risk score that should be immediately improved (the Glueing workstations, the Primering workstations, and the Leaching workstations). Specific improvements that need to be made are: First, for the Glueing workstation they include the use of APD and the addition of an air suction device, for the Primering workstation the use of APD and a Gleco Trap for liquid storage; Second, for the Laundering workstation the use of APD, and for the Emboss workstation the improvement consists of making additional buttons.